Combination of conformal mapping with variable discrete ordinates method for solving the radiation heat transfer in concentric spherical media. (November 2022) - Sarvari, S.M. Hosseini
Abstract: The radiation problem in one-dimensional participating media between two concentric spheres is solved by mapping the concentric spherical domain into the plane-parallel domain, where the radiative rays propagate along curved paths. The computational plane-parallel domain is discretized into slices with constant radiative properties and the angular domain for each control volume is discretized into variable polar angles. To validate the accuracy of the present method, comparisons are made with the previous studies in literature.